82.2k views
0 votes
What is the remainder to x^3+4x^2+x-6 divided by (x-1)

User Snowbound
by
5.4k points

1 Answer

6 votes


x^3=x^2\cdot x, and
x^2(x-1)=x^3-x^2. This gives a remainder of


(x^3+4x^2+x-6)-(x^3-x^2)=5x^2+x-6


5x^2=5x\cdot x, and
5x(x-1)=5x^2-5x. This gives a new remainder of


(5x^2+x-6)-(5x^2-5x)=6x-6


6x=6\cdot x, and
6(x-1)=6x-6. This gives a new remainder of


(6x-6)-(6x-6)=0

and so there is no remainder.

###

Quicker method: Use the polynomial remainder theorem, which says the remainder upon dividing a polynomial
p(x) by
x-c is
p(c). Here we have


p(x)=x^3+4x^2+x-6


c=1\implies p(c)=1+4+1-6=0

User Nuwan
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.